Building a Scale to Measure the Psychological Effects of the COVID -19 Coronavirus on Omani University Students - Al Qassabi, Khalifa Ahmed Humaid; Al Dhuhli, Rabia Al Mur; Qassabi, Aaisha Khalifa Ahmed Al (International Journal of Educational Studies, 2021)
The world was surprised by the outbreak of the COVID-19 pandemic. The pandemic started in China and rapidly spread in the world. This pandemic impacted different aspects of life such as the economy, health, and social life. The study aimed to build a tool to measure the psychological effects of the corona COVID-19 pandemic on Omani university students. The sample of the scale consisted of (566) students from different Omani universities. The researcher used an electronic method to distribute the questionnaire, which was Google Drive. Fifty-nine factors were used in its initial form to measure the psychological effects of the pandemic on Omani university students. The results showed that the tool is an appropriate indication of validity and reality. They revealed the results of factor validity and face validity on a scale consisting of (45) items divided into five areas: thinking about the future, pressures resulting from the requirements of the study, restrictions of movement and communication, and concern about the disease. The study recommended that student councilors and people in charge of Omani universities can use this measure to overcome the psychological effects of the pandemic on students and conduct other studies to verify the applicability to other samples.